Pengaruh Social Media Marketing, Brand Awareness, dan Brand Image Terhadap Loyalitas Pelanggan (Studi Kasus Pada Toko Havefun Store Malang) - Widiarti, Refinda Cahyu; Mawardi, M. Cholid; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Social Media Marketing, Brand awareness, and Brand Image on customer loyalty at Havefun Store. In an era of increasingly fierce business competition and digitalization, understanding the factors that drive customer loyalty is crucial, especially in the dynamic shoe industry. This study collected data through questionnaires administered to 80 Havefun Store customers, demonstrating the use of a quantitative approach. The research hypothesis was tested using multiple linear regression analysis. The analysis revealed that Social Media Marketing, Brand awareness, and Brand Image influence customer loyalty. These findings indicate that Havefun Store's efforts in utilizing social media for marketing, building strong Brand awareness, and maintaining a positive Brand Image play a significant role in retaining its loyal customers. The implication of this study is that Havefun Store is advised to continue improving its Social Media Marketing strategy, strengthening Brand awareness through innovation, and maintaining a good Brand Image through responsive service to continuously increase customer loyalty. Future research is recommended to expand the scope of the sample and population and consider other factors for more comprehensive results Keywords: Social Media Marketing, Brand awareness, Brand Image, Customer Loyalty.